Taxonomic revision of Burmeistera (Campanulaceae-Lobelioideae) in Colombia - González, Favio (Phytotaxa, 2023)
The taxonomic revision of Burmeistera (Campanulaceae, Lobelioideae) in Colombia comprising 57 species (42 of them endemic to the country) is here presented, along with a key for identification, maps of distribution, comments on the habitat, conservation status, phenology, and illustrations. Twenty species are considered as Critically Endangered, mostly due to the reduced number of individuals, the low number of flowering branches and flowers per individual, the narrow areas of distribution, and the habitat destruction. Burmeistera microphylla is reported for the first time from Colombia. Vernacular names and uses for some species are also provided. Additionally, 16 names are subsumed as new synonyms, and 15 lectotypes and one neotype are designated.